2020
DOI: 10.1039/d0py00048e
|View full text |Cite
|
Sign up to set email alerts
|

Functionalization of amine-cured epoxy resins by boronic acids based on dynamic dioxazaborocane formation

Abstract: Functionalization of epoxy resins after curing was performed based on dynamic dioxazaborocane formation between intrinsic diethanolamine units in amine-cured epoxy resins and boronic acid modifiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Similar trends were observed for the ultimate tensile strength data of D R 100 (Fig. 11a) with the preand post-recycling results for D80/D R 80 and D100/D R 100 statistically indistinguishable from each other (30)(31)(32)(33)(34)(35)(36)(37)(38). Again, whilst the A 3 control demonstrated higher strength (68-69 MPa), the results for the epoxy-amine-dioxazaborocane were very promising.…”
Section: Mechanical Recyclingsupporting
confidence: 79%
See 1 more Smart Citation
“…Similar trends were observed for the ultimate tensile strength data of D R 100 (Fig. 11a) with the preand post-recycling results for D80/D R 80 and D100/D R 100 statistically indistinguishable from each other (30)(31)(32)(33)(34)(35)(36)(37)(38). Again, whilst the A 3 control demonstrated higher strength (68-69 MPa), the results for the epoxy-amine-dioxazaborocane were very promising.…”
Section: Mechanical Recyclingsupporting
confidence: 79%
“…5a and b, non-smooth decline in E 0 and E 00 ). Given the wellestablished exchange reaction of boronic esters with diols and amino-diols 18,38,41 it is proposed that these transitions are related to rapid bond exchange reactions and related rapid topological rearrangements, between 'occupied' (dioxazaborocane) and 'unoccupied' (b-amino diol) groups, enabled by the transition of the materials from the glassy to rubbery material state. It has been suggested that, when the topological freezing temperatures (T v ) is significantly lower than T g , facile topological rearrangements would be expected at T 4 T g .…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, a postpolymerization modification method was developed to achieve the modification and functionalization of epoxy resins by the reaction between a diethanolamine (DEA) unit and boronic acid (Figure a). , The linear epoxy polymer (EP) with a DEA unit was first synthesized from the ring-opening polycondensation between diglycidyl ether of bisphenol A (DGEBA) and aliphatic propylamine. Subsequently, the EP precursor was treated with various boronic acids, such as 4-methylphenyl boronic acid and anthracene boronic acid.…”
Section: Synthesis Of Polymers Containing N→b Dative Bondmentioning
confidence: 99%
“…In this context, the implementation of functional reactive crosslinks that are able to (re)form and dissociate or rearrange reversibly to overcome the inherent non‐recyclability of covalently cross‐linked polymer networks is an interesting strategy. This concept, commonly referred to as covalent adaptable networks (CANs), [ 3 ] has been explored for a number of different cross‐linked materials and considered for broad applications ranging from polymer processing, [ 4 ] creation of composites, [ 5 ] welding, [ 6 ] or adhering [ 4a,7 ] to structuration, [ 8 ] enabling significant technological advancements that address societal interests in sustainable materials. Vitrimers, pioneered by Leibler and co‐workers in 2011, are a unique and promising class among these CANs.…”
Section: Figurementioning
confidence: 99%